SOURSOP LEAF DECOCTION ON REDUCING PAIN SCALE IN GROUP ELDERLY WITH GOUT ARTHRITIS IN PUSKESMAS ANDALAS - Khairul Andri (Menara Ilmu, 2017)
The World Health Organization estimates that about 335 million worldwidepeople suffer from gout arthritis, while in Indonesia reaches 677 888. The data from Padang  Health Department in 2015, thehighest case of gout arthritis was Andalas health center. The study aims to determine the soursop leaf decoction in reducise pain scale for elderly gout arthritis people in Andalas health centre. This study design was pre experimental with One group pretest-posttes design. The study population was all elderly with gout arthritis and10 of them were study sample. Data collected by observation and measurement pain scale. Univariate and Bivariate analysis were used by mean and standard deviation and dependen test T-test  The research found that, mean given soursop leaves boiled water beforewas 6.00 (standard deviation of 1.054) and after was 3.80 (standard deviation of 1.687). the p-valueof dependent T-test results were 0,0000 (p Value <0.05) that mean the significant between gived soursop leaves boiled water and gout arthritis pain scale for elderly. So the Chief of Andalas health centre should be used this result to make a better program especially about using herbal therapy for gout arthritis insident and train the personal how to use soursop leaf deductionby health cadre. For the further researchersare hope to follow up this results with more operational research using more samples or other methods Keywords: gout pain, soursop leaf decoction, elderlyThe reading list: 27 (2007-2015)